Numerical prediction of the incoming heat fluxes on firefighter protective clothing - Dahamni, Salim (2020)
The present study is a numerical attempt for the prediction of the incoming thermal flux on a firefighter protective clothing. The study focuses on ventilation conditions impact on the incident fluxes reaching the external garment’s face. A radiative and convective transfer modelling is considered for a 3D geometry compartment, equipped with a door, a window and subject to a localized fire, with stationary heat release rate (HRR) during a prescribed exposure time. An additive constraint on oxygen mass fraction threshold is considered to account for flame extinction. The outer layer of the protective garment is modeled as a solid medium, featuring both front (chest F) and rear (back R) sensors. The baseline case corresponds to a situation where the external temperature of the protective clothing and that of the fresh air adjacent to the firefighter's body are maintained at 25 °C. Despite the importance of mechanical ventilation devices in smoke clearance and temperature attenuation, critical values for ventilation flow rates may lead to tremendous heat fluxes revealing the apparition of backdraft situations